Bacterial degradation of waste coal - Madikiza, Lwazikazi (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2014)
As an energy source coal has one of the largest agglomerations in the world. Consequently mining of coal creates large volumes of waste in the form of low ranks coals. The complex structure of coal makes it difficult for the microorganisms to degrade and relatively few bacteria and fungi have been shown to break down coal. This study aimed to investigate bacteria not previously known to degrade coal. In this study bacteria were isolated from hydrocarbon contaminated sites and inoculated in coal medium where coal served as the only carbon source. Three strains produced a yellow "“ brown supernatant after 14 d of incubation at 30 Â°C. Bacteria generating a yellow "“ brown coloured supernatant were presumed to possess coal degrading capabilities and the best performing of these bacterial species was identified using 16s rDNA as Bacillus flexus. Scanning electron microscopy showed that there was a close association between the bacterium and substrate coal. The close association of bacteria to substrate suggested that these organisms were able to maximize solubilisation. FT-IR spectroscopic analysis demonstrated the addition of single bonded compounds COOH, OH, CN and CH that were absent prior to bacterial interaction. The increase in oxygen rich regions indicated degradation of the coal substrate. Elemental analysis showed that there was a decrease in carbon content from 47 % to 24 % during the 14 day incubation period. Reduction in coal carbon content was assumed to be due to bacterial utilization for metabolism and growth particularly as untreated coal substrate showed minimal loss of carbon. Analysis of the residual culture medium revealed that there was a linear increase in humic-like substance concentration for 8 d, coincident with increased coal biosolubilisation and colour change. Laccase activity was insignificant, and at 13 d enzyme activity was only 5Ã—10-3 U/L suggesting that B. flexus may use a different mechanism to degrade coal. Residual culture medium remaining after bacterial action on the coal substrate appeared to possess plant growth promoting activity. This soluble biodegradation product with characteristics similar to humic acid-like substances was shown to impact growth of radish cotyledons. Expansion of isolated radish cotyledons was enhanced by 140% when incubated in coal biodegradation product. In conclusion, this study has yielded B. flexus and two other unidentified bacteria, isolated from polyaromatic hydrocarbon contaminated soils, and demonstrated the ability of these microorganisms to degrade waste coal. Further studies to elucidate the mechanism of coal breakdown by B. flexus, synergies with other coal degrading microorganisms, and incorporation of bacterium into Fungcoal bioprocess technology is imminent.
Keywords: Uncatalogued